DOP44 Long-term use of ozanimod in patients with moderately to severely active Ulcerative Colitis. (21st January 2022) - Danese, S; Colombel, J F; Ponich, T; Jovanovic, I; Bossuyt, P; Longman, R; Alekseeva, O; Petersen, A; Chitkara, D; Marta, C; Charles, L; Rubin, D T; et al.
Abstract: Background: Ozanimod was approved by the FDA to treat patients (pts) with moderately to severely active Ulcerative Colitis (UC) based on the results from the 52-week (wk) phase 3 True North (TN) study. We sought to evaluate long-term efficacy and safety of ozanimod. Methods: We examined data from an interim analysis of pts in the TN parent study who entered the ongoing TN open-label extension (OLE). Pts entered the TN OLE from the phase 3 TN study if they were non-responders at the end of induction, lost response during maintenance, or completed maintenance treatment, or from the phase 2 Touchstone OLE if they remained at study closure and received once-daily oral ozanimod 0.92 mg (equivalent to ozanimod HCl 1 mg). Clinical remission, clinical response, endoscopic improvement, and corticosteroid (CS)-free remission were evaluated at Wks 46, 94, and 142 in the TN OLE for all pts who entered the OLE from the TN parent study, and in the subset of pts in clinical response at the OLE entry. The data were analysed in the intent-to-treat population using observed cases (OC), which used the number of pts remaining in the study at the corresponding time point, and non-responder imputation (NRI), which used the number of pts remaining in the study at the corresponding time point and those who withdrew before the time point but would have reached the time point if they had stayed. Treatment-emergent adverse events were evaluated from the pooled phase 2 and phase 3 UC studies. Results: A total of 823 pts from TN entered the TN OLE; as of the cut-off date (Sept 30, 2020), 64% completed Wk 46, 34% completed Wk 94, and 14% completed Wk 142 of the OLE. The most common reason for discontinuation was lack of efficacy (21%). Baseline demographics were similar as in the TN study. A total of 261 pts were in clinical response at the time of OLE entry. OC analyses showed that the percentage of pts achieving clinical remission, clinical response, endoscopic improvement, and CS-free remission was maintained over time (Table). Efficacy in the responders was higher compared to the total population and was comparable within the endpoints at Wks 46 and 94. Using the more conservative NRI analysis, the proportion of pts achieving each endpoint was lower than in the OC; however, after 94 wks of OLE treatment, 34% of all pts and 55% of the responders still maintained clinical response. No new safety signals were seen with longer-term ozanimod use in the 1158 pts in the pooled population. Conclusion: UC pts from the phase 3 TN study demonstrated maintenance of response with long-term ozanimod treatment. These data reflect approximately 2 years of additional ozanimod treatment, with no new safety signals identified.